Osteochondral Lesions of the Distal Tibial Plafond: A Systematic Review of Lesion Locations and Treatment Outcomes. Issue 4 (13th April 2021) - Allahabadi, Sachin; Allahabadi, Sameer; Allala, Ruthvik; Garg, Kartik; Pandya, Nirav K.; Lau, Brian C.
Background: Osteochondral lesions of the tibial plafond (OLTPs) remain less common than osteochondral lesions of the talus (OLTs), but recognition of the condition has increased. Purpose: To systematically evaluate the literature on lesion locations and treatment outcomes of OLTPs, whether in isolation or in combination with OLTs. Study Design: Systematic review; Level of evidence, 4. Methods: A search was performed using the PubMed, Embase, and CINAHL databases for studies on lesion locations or with imaging or treatment outcomes of OLTPs. Case reports and reports based on expert opinion were excluded. Lesion locations as well as outcome measure results were aggregated. The Methodological Index for Non-randomized Studies score was used to assess methodological quality when applicable. Results: Included in this review were 10 articles, all published in 2000 or later. Most studies were evidence level 4, and the mean Methodological Index for Non-randomized Studies score was 8.6 (range, 8-10). Overall, 174 confirmed OLTP cases were identified, and the mean patient age was 38.8 years. Of the 157 lesions with confirmed locations, the most common was central-medial (32/157; 20.4%). Of 6 studies on treatment outcomes, all but 1 evaluated bone marrow stimulation techniques. Microfracture of small lesions (<150 mm 2 ) was the most common treatment utilized. Imaging and functional outcomes appeared favorable after treatment. The data did not support differences in outcomes between isolated OLTPs and OLTPs with coexisting OLTs. Conclusion: Osteochondral lesions of the distal tibia most commonly occurred at the central-medial tibial plafond. Microfracture of small lesions was the most common treatment utilized, and clinical and magnetic resonance imaging results were favorable, although data were heterogeneous. Areas for future research include the following: the effect of patient factors and additional pathologies on outcomes; larger or deeper lesion treatment; more direct comparisons of outcomes between kissing or coexisting lesions and isolated lesions; and head-to-head comparison of treatments, such as microfracture, bone marrow–derived cell transplantation, and osteochondral autografts/allografts.